Arterial hypertension specific patient-reported outcome measure. Part I: development and primary evaluation - M. V. Ionov; N. E. Zvartau; E. A. Dubinina; A. O. Konradi (Российский кардиологический журнал)
Aim. While essential hypertension (HT) is highly prevalent and health-care is on its way to be value-based, there still no Russian-language tools to assess health-related quality of life (HRQoL) exclusively in hypertensive patients. The aim of this first part of the study was to develop and primarily evaluate a new core HT-specific patient-reported outcome measure (PROM).Material and methods. HT-specific PROM was established in several steps. As a first step conceptual framework was developed and quantity of domains and subdomains was determined. Psychometrics were also instituted for the whole scale. Next, the primary item pool was built via selection from open-access Russian-language generic and English-language specific PROMs (the latter proceeded with double-translation). Moreover some newly developed HT-specific items were introduced into scale. Finally the item pool was revised according to small pilot survey with subsequent experts’ scrutiny. Results. Four experts, three in HT, one in clinical psychology constituted the expert panel. After an iterative process of literature searches 14 relevant questionnaires were selected to build 264-item pool with five-point Likert response scales (poor to better HRQoL) with a global score. Based on conceptual framework 4 key domains (physiology, psychology, social, treatment) and 24 subdomains were drafted. On the basis of onsite and extra-mural interviews with 30 hypertensive patients (18 females, mean age 62,1±10,5 years old, 1-3 severity grades) extra questions on symptoms, psychological and social burden were developed and incorporated into corresponding domains. PROM draft underwent small pilot survey (n=50, 32 females, mean age 58,3±9,6 years old, 1-3 severity grades) and then was further revised, simplified by expert panelists. The initial PROM consisted of 163 items of which 36 were HT-specific.Conclusion. The forming HT-specific PROM is intended to measure basic HRQoL, elicit the differences between hypertensives with any stage and assess HRQoL dynamics in response to treatment. Further work will be focused on conducting a large-scale survey with PROM’ primary version.